Language and gender in academic documents - Tapia-Arizmendi, Margarita; Romani, Patrizia (Convergencia (Toluca de Lerdo, Mexico), 2012)
The aim of this article is to reflect on linguistic sexism, a kind of discrimination that has women as an object and language as an instrument. Sexist language either ignores women, or treats them as men, or represents them as an exception; such a use of language, which excludes or minimizes some social subjects, linguistically represents their self-denial and contributes to the permanence of common prejudices. The article analyzes two aspects of linguistic sexism: some asymmetries between masculine gender and feminine gender in the Spanish language; as well as some discriminatory linguistic expressions found in academic documents in the Autonomous University of the State of Mexico that hide or diminish the professional or student image of woman. Adapted from the source document.